2018
DOI: 10.1038/s41467-018-05742-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo phosphoproteomics reveals kinase activity profiles that predict treatment outcome in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) lacks prognostic and predictive markers. Here, we use high-throughput phosphoproteomics to build a functional TNBC taxonomy. A cluster of 159 phosphosites is upregulated in relapsed cases of a training set (n = 34 patients), with 11 hyperactive kinases accounting for this phosphoprofile. A mass-spectrometry-to-immunohistochemistry translation step, assessing 2 independent validation sets, reveals 6 kinases with preserved independent prognostic value. The kinases split the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 73 publications
3
43
0
Order By: Relevance
“…In particular, phosphotyrosine-(pTyr)-phospho-proteomics provides an opportunity for the identification of patient subgroups likely to benefit from tyrosine kinase inhibitors [10]. The potential of this high-throughput method has first been evidenced by the identification of the Anaplastic lymphoma kinase (ALK), Reactive oxygen species (ROS) and Platelet derived growth factor alpha (PDGFRα) mediated Non-small cell lung cancer (NSCLC) subtypes in 2007 [11] and just recently by identification of 6 kinases prognostic for the outcome of triple negative breast cancer [12]. We previously demonstrated that MS-based profiling of the tyrosine phosphoproteome in tumor biopsies is feasible and provides patient-specific profiles, enabling its further development for treatment selection purposes [13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phosphotyrosine-(pTyr)-phospho-proteomics provides an opportunity for the identification of patient subgroups likely to benefit from tyrosine kinase inhibitors [10]. The potential of this high-throughput method has first been evidenced by the identification of the Anaplastic lymphoma kinase (ALK), Reactive oxygen species (ROS) and Platelet derived growth factor alpha (PDGFRα) mediated Non-small cell lung cancer (NSCLC) subtypes in 2007 [11] and just recently by identification of 6 kinases prognostic for the outcome of triple negative breast cancer [12]. We previously demonstrated that MS-based profiling of the tyrosine phosphoproteome in tumor biopsies is feasible and provides patient-specific profiles, enabling its further development for treatment selection purposes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown important roles in understanding the molecular mechanism of cancers governed by phosphorylation-mediated pathways [108,109]. Zagorac et al [110] performed label-free quantitative analysis of the triple negative breast cancer (TNBC) phosphoproteome and compared relapsed and non-relapsed patients. In total 34 patient samples were lysed, digested and enriched for phosphopeptides.…”
Section: Discovery-based Studiesmentioning
confidence: 99%
“…MS-based proteomics has been used to characterize cell lines (Huang F. K. et al, 2017), to reveal novel layers of breast cancer classification (Tyanova et al, 2016;Yanovich et al, 2018), and to identify proteins involved in drug resistance (Liu et al, 2006). Furthermore, phosphoproteomics that identify phosphorylated proteins (von Stechow et al, 2015) has been used to connect somatic mutations to signaling (proteogenomics) (Mertins et al, 2016), to identify kinases signatures in TNBC (Zagorac et al, 2018), and to map drug targets for personalized treatments (Pierobon et al, 2018). These discoveries have diagnostic and prognostic potential which is worth further exploring and implementing in the clinic when phosphoproteomics methods will become common practice.…”
Section: Proteomicsmentioning
confidence: 99%